(untitled) (Lex localis - Journal of Local Self-Government, 2025)
Foreign direct investment has assumed great importance for host countries because of its positiveeffects; numerous studies have confirmed the effect of foreign investment on economic growth.The three North African countries, Algeria, Egypt, and Tunisia, have experienced similarinvestment climate conditions and are considered among the least attractive regions for foreigninvestment. Foreign investment inflows to them have remained modest, except in Egypt. Theeconometric study confirmed the existence of a positive direct relationship between inflows offoreign direct investment to North African countries and their rates of economic growth.